The Role of Supercomputing in Research: Astrophysics of Galactic Nuclei and Black Holes - Fiestas-Iquira, José Antonio (2015)
This article is based on the application of supercomputing techniques through an example in the investigation of the astronomical phenomena of evolution of galactic nuclei and black holes within the time period of the Universe’s existence. Numerical models of stellar dynamics simulations on supercomputers are essential in this area of research. This work was done in various research centers around the world, and the software employed uses N-body techniques in C ++, CUDA (Compute Unifi ed Device Architecture) and parallelized by using a MPI (Message Passing Interface). The scalability of the problem allows one to access accurate numerical models regarding the evolution of the systems of millions of stars. The results show that black holes, in all its variations, defi ne the shape and dynamics of galaxies, at times comparable to the age of the Universe, and have, for that reason, consequences in the destiny of itself.